2014
DOI: 10.1111/imj.12549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of advance directives in Australia

Abstract: Despite efforts to improve uptake of advance care planning (including AD), barriers remain. One likely trigger for completing an AD and advance care planning is undertaking a wider future planning process (e.g. making a will or financial enduring power of attorney). This presents opportunities to increase advance care planning, but steps are needed to ensure that planning, which occurs outside the health system, is sufficiently informed and supported by health information so that it is useful in the clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
94
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 13 publications
12
94
3
Order By: Relevance
“…Regarding the U.S. general adult population, a current study from Rao et al [34] analyzed data from n  = 7946 participants (aged 18+ years) from a national mail survey conducted in 2009/2010. Results showed an ADs completion rate of 26.3%, a rate that is similar to the rate reported for the German general adult population by the above mentioned telephone surveys [12, 14]) but higher than, for example, the rate that was currently observed for the Australian general adult population (14.4%; data derived from a national telephone survey conducted in 2012; n  = 2405 [5]). Regarding the older population in particular, Rao et al [34] reported an ADs completion rate of 51.2% for American adults aged 65 years and older.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding the U.S. general adult population, a current study from Rao et al [34] analyzed data from n  = 7946 participants (aged 18+ years) from a national mail survey conducted in 2009/2010. Results showed an ADs completion rate of 26.3%, a rate that is similar to the rate reported for the German general adult population by the above mentioned telephone surveys [12, 14]) but higher than, for example, the rate that was currently observed for the Australian general adult population (14.4%; data derived from a national telephone survey conducted in 2012; n  = 2405 [5]). Regarding the older population in particular, Rao et al [34] reported an ADs completion rate of 51.2% for American adults aged 65 years and older.…”
Section: Discussionsupporting
confidence: 76%
“…The same holds true for a power of attorney (POA) for health care authorizing other persons to make medical decisions if an individual is temporarily or permanently unable to make own decisions (e.g. [25]). Both ADs and POA for health care are, moreover, part of the broader topic of advance care planning (ACP), “[…] a wider process including, for example, ongoing conversations between the competent adult and their family and health professionals about goals of future care.” (White et al [5]; page 975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of AD in Australia was about 14% in one study, [1] and in a population in Canada, the prevalence of AD was 43.6% [2]. About a third of USA population have an AD [3].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, with the promotion of the National Framework for Advance Care Directives, 14% of the general population over the age of 18 have now prepared ACP documents, although marked variation exists across states [14]. Recent research in one metropolitan Australian city found that 27% of nursing home residents (mean 86.2 years) had documented ACPs [15].…”
Section: Introductionmentioning
confidence: 99%